Processing of Biodegradable Waste from Ceremonial Activities in Bali with Black Soldier Fly (BSF) Larvae - Mega Mutiara Sari; I Wayan Koko Suryawan; Iva Yenis Septiariva (Journal of Multidisciplinary Applied Natural Science, 2023)
The conducted study aimed to analyze the waste processing process from traditional ceremonies in Bali by examining the composition of the waste generated. Since most of the waste generated during these ceremonies is a biodegradable organic material, it is feasible to use sustainable bioconversion techniques such as Black Soldier Fly (BSF) larvae to convert this waste into useful products. In the study, a feeding trial was conducted using a garbage blender consisting of banana fruit, rice, banana leaf, coconut leaf, and flower wastes. The BSF larvae were fed at a rate of 40 mg/larvae per day with a total of 200 larvae. The researchers measured the key processing parameters including overall degradation (OD), waste reduction index (WRI), and feed conversion efficiency (ECD) which resulted in values of 41.27±0.42%, 3.30±0.03 g/day, and 7.82±0.43%, respectively. The study found that the dry residue produced during the process was around 30-31% and met the minimum standards set for compost or biomass fuel. Additionally, the total mass of BSF larvae produced was around 16-18% in one cycle, which is a high protein source that can be used to feed animals.